A rare case of mediastinal lymphatic venous malformations in children. Issue 12 (24th November 2021) - Tovichien, Prakarn; Kaeotawee, Phatthareeda; Udomittipong, Kanokporn; Pacharn, Preeyacha; Ruangchira‐urai, Ruchira
Abstract: We report a case of mediastinal lymphatic venous malformations (LVM) in a 11‐year‐old boy who presented with chest pain after jumping into a swimming pool, with review of the literature. A superior mediastinal mass was incidentally found from the chest x‐ray. Chest computed tomography revealed a large heterogenous mass at the left‐sided mediastinum containing fat, minimal enhancing solid portion, non‐enhancing cystic portion and calcification. Because of the large size of the mass, the patient underwent tumour removal. Operative findings gave a definitive diagnosis of mediastinal LVM. The patient had an uneventful clinical course and was discharged without complication. This report highlights that it is possible to misdiagnose mediastinal LVM especially if its predominant portion is lymphatic tissue with only minimal contrast enhancement. Tissue biopsy must be avoided because it may lead to haemorrhagic complication. Abstract : This report highlights that it is possible to misdiagnose mediastinal lymphatic‐venous malformation especially if its predominant portion is lymphatic tissue with only minimal contrast enhancement. Tissue biopsy must be avoided because it may lead to haemorrhagic complication.